Serological responses to koi herpesvirus (KHV) in a non‐cyprinid reservoir host. Issue 8 (11th May 2021) - Michael Bergmann, Sven; Dabels, Juliane; Klafack, Sandro; Jin, Yeonwha; Lee, Pei‐Yu; Hofmann, Arndt Christian; Wang, Yingying; Wang, Qing; Li, Yingying; Zeng, Weiwei; Lusiastuti, Angela; Zheng, Shucheng; et al.
Abstract: Koi herpesvirus (KHV) is a highly contagious virus that causes KHV disease (KHVD) inducing high mortality in carp and koi ( Cyprinus carpio L.). In the late stage, latency occurs with very low, often non‐detectable virus concentrations, which represents a challenge for virus detection. After validation according to OIE recommendations, an antibody ELISA was established to recognize antibodies of C .  carpio against KHV infection. In this study, the ELISA was modified to detect anti‐KHV antibodies from a non‐cyprinid fish. Experimentally infected rainbow trout ( Oncorhynchus mykiss ) were able to transmit KHV to naïve carp at two different temperatures, demonstrating their potential as a reservoir host. At 20°C, KHVD was induced in carp but not at 15°C. Unexpectedly, rainbow trout developed humoral response against KHV at both temperatures. In contrast to carp, at 15°C trout produced neutralizing antibodies but not at 20°C. While antibodies obtained from infected carp sera reacted in a similar way against all KHV, antibodies from rainbow trout sera reacted differently to the same isolates by ELISA. The data show that even when non‐cyprinid fish species are infected with KHV, they can produce antibodies that differ from those observed in carp.